2017
DOI: 10.1111/bju.13983
|View full text |Cite
|
Sign up to set email alerts
|

Focal irreversible electroporation as primary treatment for localized prostate cancer

Abstract: Our data support the safety and feasibility of focal IRE as a primary treatment for localized PCa with effective short-term oncological control in carefully selected men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 18 publications
3
68
1
Order By: Relevance
“…The importance of a larger treatment margin was exemplified in a prospective cohort study of 123 patients with predominantly intermediate-risk prostate cancer and a median follow-up of 36 months [30,31]. In this study, no Clavien-Dindo Grade III-IV adverse effects occurred.…”
Section: Clinical Trials Of Ire In Prostate Cancermentioning
confidence: 78%
See 1 more Smart Citation
“…The importance of a larger treatment margin was exemplified in a prospective cohort study of 123 patients with predominantly intermediate-risk prostate cancer and a median follow-up of 36 months [30,31]. In this study, no Clavien-Dindo Grade III-IV adverse effects occurred.…”
Section: Clinical Trials Of Ire In Prostate Cancermentioning
confidence: 78%
“…Another recent prospective cohort study of 30 patients, with a median follow-up of 20 months, reported similar oncological and function outcomes [32]. The results of studies applying IRE are shown in Table 2 [22][23][24][25][26][27][30][31][32]37,48].…”
Section: Clinical Trials Of Ire In Prostate Cancermentioning
confidence: 85%
“…The initial feasibility trials with IRE demonstrated the safety and feasibility of this new technique with low patient morbidity and good short-term oncologic control (7)(8)(9)(10)(11)(12). IRE ablates tumor tissue by delivering a direct high-voltage current between a pair of needle electrodes (13).…”
Section: Resultsmentioning
confidence: 99%
“…Since all the prostate segments can be encompassed within the needle configurations of IRE, oncologic control should not theoretically differ between the prostate segments. Failures after IRE were recently proven to be significantly dependent on the applied safety margin and/or system errors that occurred during the treatment (12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation